Effect of using appendectomy surgical simulation software on academic achievement: Game-based learning during the COVID-19 pandemic - Sara Bagheri; Senthilkumar Jagatheesan; Mahdi Ghanati; Amin Sedigh (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Regarding the urgent needs of students for an efficient teaching methodology, it is necessary to use self-directed and self-centered teaching methods that encourage the power of reasoning and judgment. This study aimed to investigate the effect of using the game-based Appendectomy Surgical Simulation software on the academic achievement of undergraduate operating room students in Khomein, Iran. Materials & Methods: This quasi-experimental study was conducted during the COVID-19 pandemic. Forty undergraduate operating room students who were in the second semester of the first year of the operating room undergraduate program participated in this quasi-experimental single-blind study. The participants were assigned randomly to the control and intervention groups after their consent was obtained. Following the use of the game-based Appendectomy Surgical Simulation software for the intervention group and lecture-based classes on a specific academic learning software for the control group, the data were collected using a researcher-made questionnaire concerning academic achievement, whose validity and reliability were approved. The data were then analyzed using descriptive and analytical tests in IBM SPSS (version 22) at a significance level of P<0.05. Results: The average score of academic achievement was significantly higher in the intervention group (58.35±2.38) than in the control group (35.65±4.14) (P<0.05). Conclusion: Using the game-based Appendectomy Surgical Simulation software has been effective in improving the academic achievement of students during the COVID-19 pandemic and afterward. Therefore, it can be used in academic and educational programs.